Safety Evaluation of Yeasts With Probiotic Potential - Fernández-Pacheco, Pilar; Ramos Monge, Inés María; Fernández-González, Mónica; Poveda Colado, Justa María; Arévalo-Villena, María (Frontiers in Nutrition, 2021)
This work has evaluated the safety aspects of 20 yeast strains, isolated from food environments, selected in previous works due to their probiotic potential. Among the different strains, there are Saccharomyces and non-Saccharomyces yeasts. Before safety evaluation, differentiation of Saccharomyces cerevisiae strains was done by PCR amplification of inter-δ region with pairs of primers δ2-12 and δ12-21, which showed that they were all different from each other and also had different profiles to Saccharomyces boulardii (the only commercial probiotic yeast). The non-Saccharomyces ones were already known. The evaluation tests carried out were antibiotic and antifungal resistance, production of biogenic amines, deconjugation activity of bile salts, and different enzymatic activities: coagulase, deoxyribonuclease, hemolysin, proteolytic, and phospholipase. None of the studied strains demonstrated coagulase, hemolytic or DNase capacity (clear virulence factors), although all of them showed protease activity, some showed phospholipase activity, and half of the yeasts were capable of conjugating bile salts. Regarding antimicrobial compounds, all were resistant to antibiotics but showed sensitivity to the antimycotics used. Nevertheless, only one strain of Hanseniaspora osmophila was excluded for use in the food industry, due to its high production of tyramine.